Pyrethrin from Tanacetum cineriifoliun as repellent against mosquitoes - Amrutha, Peneremmal; Priya, Balakrishnan Sathya; Lakshmanasenthil, Shanmugaasokan; Jenifer, Antonythiraviam Anne; Pillai, Laxmi Satheesh; Suja, Gunasekaran; Vinothkumar, Thirumalairaj (International Current Pharmaceutical Journal, 2013)
The present study is conducted to find the efficacy of plant extracts to act as mosquito repellents. Initially, the larvicidal activity of the extracts and the toxicity study was conducted. From the results, the extracts with maximum larvicidal activity and the minimum toxicity were used for the further analysis. The least toxicity was observed with the ethanol extracts of Lantana camara, Tagetes erecta and Tanacetum cineriifolium. The Lanatana camara and Tanacetum cineriifolium showed the maximum larvicidal activity. The DNA sugar damage assay is performed and read at 532 nm. The hemolytic activity of the extract is conducted and the results indicate that the extracts showed no hemolytic activity at the concentration of 100 and 200mg/L. Only the flower extracts of Tagaetes erecta, Lantana camara and Tanacetum cineriifolium showed moderate hemolytic activity at 500 and 1000 mg/L. Finally, the HPLC analysis of the extracts showed that the ethanol extracts of Lantana camara and Tanacetum cineriifloium revealed the presence of marker compound. Therefore the ethanol extracts of Lantana camara and Tanacetum cineriifolium were taken up for the membrane stabilization assay. The skin irritation potential of the cream prepared using the ethanol extract of Tanacetum cineriifolium was analysed, the cream showed no irritation. DOI: http://dx.doi.org/10.3329/icpj.v2i10.16411 International Current Pharmaceutical Journal, September 2013, 2(10): 170-176